PERISTILAHAN TUMBUHAN DALAM PERIBAHASA MASYARAKAT MELAYU SAMBAS - Afriyanti Afriyanti; Patriantoro Patriantoro; Agus Syahrani (Universitas Tanjungpura, 2017)
AbstractThe terminology of plants in the Sambas malay society proverb in this study is seen from the form, the lexical meaning, the meaning of the analogy, and the cultural meaning. The method used in this research is descriptive linguistics. The approach used in this research is the ethnolinguistic approach. The data source of this research are primary data and secondary data. Primary data of this study were taken from the field orally from informants. Secondary data in this research is the data written as corpus data obtained from the book